The AI Revolution: How Artificial Intelligence is Fundamentally Changing the Pharmaceutical Industry - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The pharmaceutical industry, a cornerstone of global health, has long been characterized by a profound paradox: the immense cost, protracted timelines, and h...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation